2-(2-Nitrovinyl) furan exacerbates oxidative stress response of Escherichia coli to bacteriostatic and bactericidal antibiotics. (March 2018) - Ajiboye, T.O.
Abstract: The influence of 2-(2-nitrovinyl) furan on the activities of selected bacteriostatic and bactericidal antibiotics was investigated. Minimum inhibitory concentration and fractional inhibitory concentration index were determined to evaluate the interaction between 2-(2-nitrovinyl) furan and the antibiotics. 2-(2-nitrovinyl) furan exhibited additive interactions with chloramphenicol, erythromycin, lincomycin and gemifloxacin. However, synergistic interaction was observed with amoxicillin, ampicillin and ciprofloxacin. Superoxide anion content of Escherichia coli exposed to antibiotics with/without 2-(2-nitrovinyl) furan increased significantly ( p  < .05). Furthermore, reduced glutathione decreased significantly with a corresponding increase in glutathione disulphide. In addition, malondialdehyde, a product of lipid peroxidation, increased significantly in E. coli exposed to antibiotics and 2-(2-nitrovinyl) furan. It can be deduced from this study that 2-(2-nitrovinyl) furan enhanced bacteriostatic and bactericidal antibiotics-mediated bacterial death possibly by potentiating reactive oxygen species generation and oxidative stress. Highlights: 2-(2-Nitrovinyl) furan increased antibiotic susceptibility. 2-(2-Nitrovinyl) furan enhanced superoxide generation. 2-(2-Nitrovinyl) furan enhanced antibiotic-mediated glutathione depletion. 2-(2-Nitrovinyl) furan enhanced antibiotic-mediated increase in malondialdehyde.